Clutch predation in relation to nest density in Mallard and Tufted Duck - Hill, David A (Wildfowl, 1984)
Clutch predation in relation to Mallard Anas platyrhynchos and Tufted Duck Aythya fuligula nest density was studied at two inland lakes. A between year analysis for one site showed that the proportion of Mallard nests destroyed by predators, mainly Carrion Crows Corvus corone, Magpies Pica pica and rats Rattus norvegicus, increased with an increase in nest density. The number of nests in existence at any one time changed continually because of predation, desertion, hatching or new nests being started. Nests of both species were aggregated in patches of tall vegetation on the one site where the analysis was possible. There was evidence that nests closer together (i.e. where nests were at high density) were less successful than those further apart. Tufted Duck nests were closer to another nest than those of Mallard.